2003
DOI: 10.1007/s11746-003-0744-7
|View full text |Cite
|
Sign up to set email alerts
|

The study of oxazolidone formation from 9,10‐epoxyoctadecane and phenylisocyanate

Abstract: The formation of oxazolidone from 9,10-epoxyoctadecane and phenylisocyanate was studied. One branch of epoxidized vegetable oil with one epoxy group per chain corresponds to 9,10-epoxyoctadecane. This model could explain the probability of oxazolidone formation from natural oil-derived epoxides. Epoxidized natural oils are TG consisting of glycerin and three FA with or without one to three epoxy groups in the middle of the chain. To study oxazolidone formation from an internal epoxy group without possible inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Fourier Transform Infra Red analysis was used to examine the functional groups present in the polyurethane foam. The carbonyl group of the oxazolidone ring appeared gradually from foam 9 to foam 0 at around 1,750 cm -1 [18] (Fig. 4).…”
Section: The Effects Of Ooc In Diethanolamides On Polyurethane Foammentioning
confidence: 94%
See 2 more Smart Citations
“…Fourier Transform Infra Red analysis was used to examine the functional groups present in the polyurethane foam. The carbonyl group of the oxazolidone ring appeared gradually from foam 9 to foam 0 at around 1,750 cm -1 [18] (Fig. 4).…”
Section: The Effects Of Ooc In Diethanolamides On Polyurethane Foammentioning
confidence: 94%
“…But in foam 10, produced by diethanolamides synthesized by RBDPKO o only, the carbonyl group of oxazolidone was not detected. In the study of the reaction between aromatic isocyanate and a fatty epoxide, where the epoxy groups were in the middle of the chain, AlCl 3 Lewis acid is the most efficient converter of oxazolidone when compared with other catalysts, namely lithium chloride and zinc iodide [18]. In view of these results, we selected AlCl 3 -THF complex as catalyst so that the thermally stable oxazolidone can be introduced into the polyurethane backbones.…”
Section: The Effects Of Ooc In Diethanolamides On Polyurethane Foammentioning
confidence: 99%
See 1 more Smart Citation
“…Many different types of catalysts in the reaction between 9, 10-epoxyoctadecane and phenylisocyanate to form oxazolidone have been Scheme 1 Reaction scheme of the synthesization of diethanolamide. R 1, R 2 , R 3 are the alkyl chains with or without epoxide(s) functionality [16]. Other study reported on improved compressive strength of epoxy modified polyurethane rigid foams by reacting epoxy resin, isocyanate, and additives at 80°C for 24 h [17].…”
Section: Synthesis Of Diethanolamidesmentioning
confidence: 99%
“…Yaganeh and co-workers reported that the introduction of oxazolidones to polyurethane backbone from reacting glycidol with isocyanate-terminated polyurethane prepolymers improved the thermal and the stress-strain properties of the elastomers [12] . Although the epoxy groups in the middle of the fatty acid chain of triacylglycerides have lower reactivity towards isocyanate, Javni and co-workers found that the yield of oxazolidones is actually dependent on the type of catalyst used [13] .…”
Section: Introductionmentioning
confidence: 99%